Group portrait of the attendees of the 1956 Methodist C.A. Camp #1 at Monte Toyon - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the Methodist C.A. Camp #1, held at July 21-28, 1956 at Monte Toyon in Aptos, California. The group can be seen assembled out of doors, with about half of the group members standing in front of a bus (right side of image).